ANALISIS STRUKTUR ATAS GEDUNG PONPES MU’ALIMIN TERHADAP BEBAN GEMPA MENGGUNAKAN METODE PUSHOVER ANALYSIS - Fauziah, Rahmadina; Masril, Masril; Nurhasanah Habirun, Asiya (Ensiklopedia Research and Community Service Review, 2024)
The Ponpes Mu'alimin Building located in Agam Regency, West Sumatra Province, is one of the educational infrastructure places that has a column plan whose shape and dimensions of the columns are not symmetrical. This building is also included in the earthquake risk category (risk category IV), so pushover analysis is used to analyze the behavior of building collapse against earthquakes using non-linear static analysis methods (pushover analysis) with the help of computer programs, namely SAP2000 software. The study can conclude that this building is still able to withstand earthquakes, and the possibility of human casualties is very small, according to the results of the analysis of the capacity spectrum in the x and y directions, the total deviation value, and  the maximum inelastic  deviation based on ATC-40 in 1996. This calculation belongs to the Immediate Occupancy (IO) class, with a result of < 0.01.Keywords: Pushover Analysis; Earthquake; Deviation.